Influence of light intensity on mechanical properties of the resin composite - Betsy Kilian Martins Luiz; Luiz Henrique Maykot Prates; José Roberto Bertolino; Alfredo Tibúrcio Nunes Pires (Universidade Estadual de Campinas, 2015)
The aim of this study was to evaluate Vickers micro-hardness and flexural strength, of five commercial resin composites cured by two light curing units (LCU) with different intensities. The inorganic filling content of the composite was evaluated by thermogravimetric analysis (TGA) and the morphology of the surface was analyzed by scanning electron microscopy (SEM), in composites cured by different light intensities and immersed into a commercial soft drink or distilled water. The results show an improvement in the mechanical properties when the highest intensity of the halogen light-curing unit was used. At the same intensity of LCU, the highest values for the mechanical properties were found in specimens with a higher percentage by weight of filler. The better values were observed for micro-hardness and flexural strength in hybrid resin composites than in microfill resin composites. When the material was stored in the soft drink, changes occurred in the composite structure. The SEM images show a fractured specimen immersed in the soft drink compared with the control group, maintained in distilled water. The images show the low level of light beam penetration into resin composites, since the removal of resin components at the central part of the specimen was higher than at the surface near the light incidence.